Fluence-to-dose conversion coefficients in a voxel rat model for external neutron irradiation - Xiaomin Zhang; Xu Xu; Yong Yuan; Jing Ning; Dawei Li; Yunlong Ji (Nuclear Engineering and Technology)
Fluence-to-dose conversion coefﬁcients based on a developed rat model have been calculated for neutrons with energies <20 MeV using Monte Carlo N-particle code (MCNP), for the purpose of neutron radiation effect evaluation. The calculation was conducted respectively for 27 monodirectional monoenergetic neutron beams in the energy range 10−9 MeV to 20 MeV, under four different irradiation conditions: left lateral, right lateral, dorsal–ventral and ventral–dorsal. The neutron ﬂuence-to-dose conversion coefﬁcients for selected organs were presented in the study and can be used to determine the organ dose of the rats experimentally exposed to external neutron irradiation. The results in this work were compared with the published data based on a mouse model to investigate the effect of size and weight difference on neutron organ dose. The comparison results showed the fluence-to-dose conversion coefficients of the rat model have the similar energy dependency and sensitivity to irradiation conditions compared with that of the mouse model, and the weight and size difference in individuals could lead to different levels of neutron organ dose difference depending on neutron energy, irradiation conditions as well as the location of organs.